Vaccine Effectiveness Against Life-Threatening Influenza Illness in US Children . (13th January 2022) - Olson, Samantha M; Newhams, Margaret M; Halasa, Natasha B; Feldstein, Leora R; Novak, Tanya; Weiss, Scott L; Coates, Bria M; Schuster, Jennifer E; Schwarz, Adam J; Maddux, Aline B; Hall, Mark W; Nofziger, Ryan A; et al.
Abstract: Background: Predominance of 2 antigenically drifted influenza viruses during the 2019–2020 season offered an opportunity to assess vaccine effectiveness against life-threatening pediatric influenza disease from vaccine-mismatched viruses in the United States. Methods: We enrolled children aged <18 years admitted to the intensive care unit with acute respiratory infection across 17 hospitals. Respiratory specimens were tested using reverse-transcription polymerase chain reaction for influenza viruses and sequenced. Using a test-negative design, we estimated vaccine effectiveness comparing odds of vaccination in test-positive case patients vs test-negative controls, stratifying by age, virus type, and severity. Life-threating influenza included death or invasive mechanical ventilation, vasopressors, cardiopulmonary resuscitation, dialysis, or extracorporeal membrane oxygenation. Results: We enrolled 159 critically ill influenza case-patients (70% ≤8 years; 51% A/H1N1pdm09 and 25% B-Victoria viruses) and 132 controls (69% were aged ≤8 years). Among 56 sequenced A/H1N1pdm09 viruses, 29 (52%) were vaccine-mismatched (A/H1N1pdm09/5A+156K) and 23 (41%) were vaccine-matched (A/H1N1pdm09/5A+187A, 189E). Among sequenced B-lineage viruses, majority (30 of 31) were vaccine-mismatched. Effectiveness against critical influenza was 63% (95% confidence interval [CI], 38% to 78%) and similar by age. Effectiveness was 75% (95% CI, 49% to 88%) against life-threatening influenza vs 57% (95% CI, 24% to 76%) against non-life-threating influenza. Effectiveness was 78% (95% CI, 41% to 92%) against matched A(H1N1)pdm09 viruses, 47% (95% CI, –21% to 77%) against mismatched A(H1N1)pdm09 viruses, and 75% (95% CI, 37% to 90%) against mismatched B-Victoria viruses. Conclusions: During a season when vaccine-mismatched influenza viruses predominated, vaccination was associated with a reduced risk of critical and life-threatening influenza illness in children. Abstract : In the largest study of its kind, vaccination averted most critical (63%) and life-threatening (75%) influenza among children aged <18 years. This reduction was impressive because vaccine components were mismatched to the 2 predominant circulating influenza strains during this season.